2012
DOI: 10.1016/j.bmcl.2011.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, cytostatic activity and ADME properties of C-5 substituted and N-acyclic pyrimidine derivatives

Abstract: The synthesis of 5-alkyl pyrimidine derivatives, 5,6-dihydrofuro[2,3-d]pyrimidines and 5-alkyl N-methoxymethyl pyrimidine derivatives and their cytostatic evaluation is described. The mechanism of antiproliferative effect and ADME profile of 5-(2-chloroethyl)-substituted pyrimidine 3 that exerted the most pronounced cytostatic activity are also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 27 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…5-chloroethyl-2,6 dichloro pyrimidine 8 (IC 50 = 0.8 ± 0.2 μM) exerted cytostatic effect on HCT-116 cancer cell line which led to cell cycle arrest at G2/M phase due to DNA damage. The SAR suggests that the presence of two aromatic and an aliphatic chlorine atom linked to the pyrimidine ring gave the compound with maximum potential [11]. Furthermore, 2-arylaminopyrimidine derivative bearing a 2amino-N-methylbenzamide at C4 and chlorine at C5 positions were designed as a potent inhibitor of c-Met in cellular and enzymatic assays.…”
Section: 4 5-trisubstituted Pyrimidinesmentioning
confidence: 99%
“…5-chloroethyl-2,6 dichloro pyrimidine 8 (IC 50 = 0.8 ± 0.2 μM) exerted cytostatic effect on HCT-116 cancer cell line which led to cell cycle arrest at G2/M phase due to DNA damage. The SAR suggests that the presence of two aromatic and an aliphatic chlorine atom linked to the pyrimidine ring gave the compound with maximum potential [11]. Furthermore, 2-arylaminopyrimidine derivative bearing a 2amino-N-methylbenzamide at C4 and chlorine at C5 positions were designed as a potent inhibitor of c-Met in cellular and enzymatic assays.…”
Section: 4 5-trisubstituted Pyrimidinesmentioning
confidence: 99%
“…The pyrimidine moiety, as one of the most important heterocyclic scaffolds, is considered a privileged structure in medicinal chemistry for drug discovery. 19,20 Pyrimidine derivatives have been reported to have a broad spectrum of biological activities, such as antiviral, 21,22 antibacterial, 23 antifungal, 24 anti-inammatory, 25,26 COX-2 inhibitors, 27 antituberculosis, 28 herbicidal 29 and insecticidal 30 activities. Moreover, previous studies have found that numerous pyrimidine derivatives exhibited promising anticancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrimidine ring is the building unit of DNA and RNA, due to which pyrimidine derivatives exhibit diverse pharmacological activities such as anticancer [2][3][4][5][6][7][8][9][10], antiviral [11][12][13] especially anti-HIV [14][15][16], antimalarial [17][18][19], antimicrobial [20,21] and anti-inflammatory [22,23]. They also exhibit activity against gonadotropin releasing hormone receptors and display herbicidal potential by inhibiting acetohydroxyacid synthase, a key enzyme in the biosynthesis of branched-chain amino acids [24][25][26].…”
Section: Introductionmentioning
confidence: 99%